Tarian lebah dalam perspektif al Qur’an surah an-Nahl ayat ‎‎68-69: Telaah peran pendidikan sains terintegritas al-Quran ‎dalam mempersiapkan pendidikan mendatang - Khumainah, Nanda Dila Zahrotul; Sholehuddin N, M. Arul; Ulum, Achmad Miftahul (Maliki Interdisciplinary Journal, 2023)
We often see insects around the environment, especially bees. It is unique, namely the special dance that bees use to guide other bees to find food. A lot of research was used to produce this bee dance theory, and this is in line with Surah An-Nahl verses 68-69. Apart from that, the development of science and technology (Science and Technology) has brought significant changes to the world of education. As a rational human nature, we have the ability to think to continue making changes. However, in dealing with the ins and outs of life, there are guidelines that are considered authentic during wa eating. Much has been revealed about the scientific knowledge of the Koran, quite a bit of science that researchers have discovered is in accordance with the holy book of the Koran. So the author is interested in discussing how the Al-Quran surah An-Nahl verses 68-69 discusses the dance of bees which theoretically is very unique. One way to prepare for education in this field of science is to read the Al-Quran. Integrating science will provide provisions in the form of resilience in adhering to the Islamic guidebook. The research method used is descriptive which is supported by literature reviews from various literature. Which shows that the scientific knowledge of the bee dance is also found in the Islamic holy book, namely the Koran, which was present hundreds of years before this theory was discovered. So education that is integrated in the Koran is considered relevant to strengthen faith and create a sense of continuing to explore and study the Koran.